Pengaruh Latihan Resistensi terhadap Tekanan Darah pada Lansia dengan Hipertensi di Puskesmas Kenten Palembang: Penelitian - Nurjanah; Anita Carlina (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Hypertension in the elderly is a health issue that increases the risk of cardiovascular diseases. Resistance training has been identified as a non-pharmacological intervention with the potential to lower blood pressure. This study aimed to analyze the effectiveness of resistance training in reducing blood pressure among elderly individuals with hypertension. A quasi-experimental pretest-posttest design was employed, involving 31 elderly participants at Kenten Health Center, Palembang. The intervention was conducted over 12 weeks with an intensity of 70–85% 1RM. The results showed that resistance training significantly reduced systolic blood pressure by 6.26 mmHg (p < 0.001) and diastolic blood pressure by 2.26 mmHg (p = 0.006). This reduction is associated with increased vascular elasticity and decreased peripheral vascular resistance. Resistance training can be an alternative strategy for managing hypertension in the elderly. However, adherence to the training program and comorbid conditions should be considered for optimal results.